"Speaking-For" and the Lack of Representation: Advocacy in Hobbes and Rousseau. Issue 2 (3rd May 2020) - Balke, Friedrich
Abstract: The article deals with the complexities and issues of modern advocacy in the political and autobiographical discourses of Thomas Hobbes and Jean-Jacques Rousseau. In his political philosophy, Hobbes speaks on behalf of a multitude which becomes a political body in the course of being represented. He acts as an advocate and a prosecutor at the same time because he conducts a trial in the name of reason against those for whom he speaks, urging them to leave the state of nature. Hobbes imagines a foundational scene in which each and everyone's discourse is reduced to the repetition of a formula that generates the 'civic state.' Rousseau, by contrast, discredits all political speech that presumes to represent [vertreten] the people by speaking in their place and thus silencing them. He establishes advocacy as a specific modality of truth-telling ( parrhesia ) involving the risk of irritating or offending those who are addressed. He develops a new form of veridiction in which infamous and inglorious, but at the same time singular lives cross the threshold of (political) representation, a process which Hobbes feared as the major reason for political dissolution. Rousseau's discourse is an effort to mobilize future advocates to take the risk of speaking for someone by speaking of themselves: Rousseau in all his singularity presents his contested life to others in such a way that they feel encouraged to speak of themselves in like fashion and, by doing so, to act as his genuine advocates.